2002
DOI: 10.1152/japplphysiol.00733.2001
|View full text |Cite
|
Sign up to set email alerts
|

Selected Contribution: Differential expression of stress-related genes with aging and hyperthermia

Abstract: Aging is associated with a reduced capacity to cope with physiological stress. To study the molecular mechanisms associated with the decline in stress tolerance that accompanies aging, differences in gene expression between young and old Fischer 344 rats under euthermic control conditions or in response to hyperthermic challenge were evaluated using a cDNA array containing 207 stress-related genes. In the nonstressed control condition, aging resulted in selective upregulation of stress protein genes and transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 32 publications
0
21
1
Order By: Relevance
“…61). Age-associated regulation of stress-response genes is an area of accelerated research, particularly with the advent of microarray technology (63). The information resulting from such research, in addition to the advances in the area of gene therapy, will be valuable in defining the roles of HSPs and other components of the stress response in aging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…61). Age-associated regulation of stress-response genes is an area of accelerated research, particularly with the advent of microarray technology (63). The information resulting from such research, in addition to the advances in the area of gene therapy, will be valuable in defining the roles of HSPs and other components of the stress response in aging.…”
Section: Discussionmentioning
confidence: 99%
“…Cells have evolved complex genetic systems to detect specific forms of stress and activate the expression of genes whose products increase the resistance of the cell to further stress and/or initiate the processes of tissue regeneration. Unfortunately, the expression of many of these genes is attenuated in aging (53,63). As a consequence, cellular responsiveness to stress diminishes with advancing age.…”
mentioning
confidence: 99%
“…In contrast to acute HS, the effects of chronic HS on gene expression and cellular metabolism have been studied only to a limited extent (Zhang et al 2002, Bhusari et al 2008. Acute and chronic HS pose two distinct challenges to animals.…”
Section: Introductionmentioning
confidence: 99%
“…During the aging process, the normal increase in the concentration of Hsp90 in response to thermal stress is attenuated in lymphocytes (4), liver cells (5), and mesenchymal stem cells (6). Diminished Hsp90 messenger RNA (mRNA) and protein synthesis following mitogen stimulation of lymphocytes with interleukin-2 (IL-2) has been measured in aged donors of T lymphocytes (7), and tissue from aged animals and blood from elderly humans show reduced production of stress proteins, including Hsp90, following thermal stress (4,8).…”
mentioning
confidence: 99%
“…Results from complementary DNA array experiments comparing liver cells from young and aged rats showed that altered gene expression in response to stress is indicative of decreased stress protein mRNA expression (5), and a 2-fold decrease in hsp90 mRNA expression has been detected in OA versus normal cartilage (9). Hsp90 is further implicated in altered homeostasis of aging articular cartilage through its requirement for proper telomerase assembly and function (10), particularly given the loss of telomere length with age in chondrocytes (11)(12)(13).…”
mentioning
confidence: 99%